Who can (still) afford to retire early? Cross-country comparison of incomes of senior workers and young retirees using LIS data for 2007 & 2010 - Petrovici, Carmen; Neugschwender, Jörg (Luxembourg, 2014)
"The aim of this paper is to compare the economic situation of young retirees with their peers who decided to continue their working life before and during the recent economic crisis using the micro-data from the Luxembourg Income Study Database (LIS) for four countries (Greece, Spain, the UK and the US) for the years 2007 and 2010. In order to have comparable samples across countries with different institutional settings, we delimit our sample to the age group up to ten years prior to the statutory retirement age. In a first section we look at the income mix of early retirees and senior workers from a gender perspective taking into account the disposable household income. In a second section, we apply multinominal logistic regression models to explain the labour market status of seniors, focusing on the income predictors, distinguishing between personal income derived from the labour market participation, other personal income and other household income. We consider as well the alternative exit pathways from the labour market such as unemployment, disability and other types of inactivity. Our results show changes over time in the impact of incomes from different sources on the labour market status of seniors as well as gendered life courses. The paper contributes to the literature by a comparative analysis of the labour market behaviour in conjunction with income from different sources before and after the crisis."